O dever de recuperar a área degradada e a compatibilidade entre desenvolvimento econômico e meio ambiente na exploração dos recursos minerais - Ferreira, Gabriel Luis Bonora Vidrih (2007)
Mining characterizes itself as an economical activity employed with a strict relation with the environment. Taking into account the exploitation of a natural resource, and due to the fact of the intimate relation between the ‘natural deposit’ and the other environmental resources of a region. Thus, the viability of the mining enterprise depends on the intervention in the area to be exploited, aiming to reach and extract the ore, being a task of the legal system to regulate the way in which the activity shall be developed in order to provide the mitigation and the compensation of the produced environmental changes, highlighting the need for the social and economical benefits to be reached with respect for the environment. Therefore, no matter how much development within the environmental quality patterns and regulations, there will always be a residual impact which necessarily operates for this activity and that is not possible to be effectively avoided. In this picture, it is the forecast of the Federal Constitution which, aiming to reduce the social ONUS and add conditions of sustainability to the mining process, contemplates those who exploit the mineral resources with the obligation of recovering the degraded environment, characterized as a compatibility regulation in the economical order maintenance with the environmental protection which has a specific treatment for the mining process. Thus, it is considered that the characteristics and the importance of mining justify a specific environmental treatment disposed by the Constitution, being the objective of the present study, analyze the existing intrinsic relation between mining and the environment, identifying through the need of recovering, the way in which the economical development and the environmental protection compatible themselves in the mining process, and their respective effects on the field of the environmental civil responsibility, in special to the establishment of a different regimen for the recovering of the environmental hazardous caused through the mining exploitation. With the prevision regarding the need of recovering, built in the mining process, the conception that this kind of mining activity corresponds to a transitory modality of soil usage, being the responsibility of the recuperation phase, provide the upgrading of the degraded area into a stabilized level that allows a further usage of the soil. In this perspective, facing the necessity of recovering, in the range of the manifestation of the civil responsibility in the mining process, certain environmental interventions seem possible to be absorbed by peculiar treatment in relation to the manifestation of the need for recovering, consubstantiated in the classification of a modality of environmental hazardous common in this productive activity, denominated `mineral environmental hazardous´. These environmental alterations inherent and indispensable for the development of the agricultural activity, at first, are considered as residual environmental impact, due to the impossibility of avoiding these occurrences and, further with the finishing of the activities or having the physical possibility of realizing any recuperation service or reduction of the environmental effects, these interventions gain juridical relevance and become to be considered as hazard or degradation, receiving, from then on, the imputation of the recovering obligation. Key words: Economical order and environment. Environmental protection in mining. Mineral environmental hazardous. Residual impact. Civil environmental responsibility.